Artificial Intelligence in Information Retrieval System - Sudha, S. (Journal of Information and Knowledge, 1986)
Artificial intelligence and information retrieval are two new developments which have mutually enhancing capabilities. Pattern Recognition, Knowledge-representation, Problem solving techniques, learning and expert systems have interplaying roles in improving the efficiency of Information Retrieval Processes. Pattern classification, user query formulation have been discussed. Statistical approach to text indexing is also discussed.